Evaluation of the Effect of Spatial Resolution on Image Quality in Phosphor Plate Systems - Özlem Üçok; Ceyda Gizem Topal; Hatice Tetik (Ankara University, 2023)
Purpose: This study aims to investigate the effect of 4 different scanning protocols offered by the VistaScan Mini Easy scanner on image quality at different exposure times. Materials amp; Methods: Four number size-2 photostimulable phosphor plates were exposed with 5 different exposure times while keeping other parameters constant. The exposed plates were scanned without delay using 4 different scanning protocols. 10 lp/mm, 20 lp/mm, 25 lp/mm, and 40 lp/mm are offered by the VistaScan Mini Easy scanner. The mean gray value was calculated using the ImageJ program by identifying three non-overlapping regions of interest from the background and each step in the obtained images. The mean of all mean gray values determined for the background and steps on a plate was also considered the mean gray value of that plate. Results: When plate mean gray values at 0.20 s and 0.40 s were examined, a statistically significant difference was observed between the scanning protocols (p lt;0.001, p=0.001 respectively). It was determined that the plate mean gray value at 40 lp/mm in 0.20 s was lower than that of other scanning protocols. The plate mean gray value at 20 lp/mm in 0.20 s was higher than that at 25 lp/mm. It was determined that the plate mean gray value at 10 lp/mm in 0.40 s was lower than that of the other groups. Conclusion: The effect of spatial resolution on diagnostics in digital imaging per se is a subject under investigation and still not agreed upon. Therefore, more studies on spatial resolution are needed.